A two-edged sword: The impact of public debt on economic growth-the case of Ethiopia - Addis Yimer; Alemayehu Geda Fole (Journal of Applied Economics, 2024)
This study investigates the dynamic effects of public debt on economic growth in Ethiopia using annual data from 1980 to 2021. The results from the Autoregressive Distributed Lag (ARDL) modeling approach reveal that while public debt boosts investment and enhances growth in the short term, it hinders long-term growth. Additionally, debt servicing negatively impacts growth in both the short and long term by diverting vital resources from investment. Thus, public debt acts as a two-edged sword for Ethiopia's economic growth. On one side, it finances infrastructure and other growth-stimulating projects; on the other, high debt levels can impede growth. To mitigate the adverse impacts of public debt, Ethiopia should implement prudent fiscal discipline, mobilize domestic revenue, manage debt efficiently, address its structural trade deficit, and prioritize needs to prevent misuse and corruption. This approach should also prioritize social spending and public investment while strategically transitioning from debt dependence.
Keywords: 330; economic growth; Ethiopia; Impact; Public debt